Effect of providing information to the patient about upper gastrointestinal endoscopy on the patient’s perception, compliance and anxiety level associated with the procedure - Seda Pehlivan,; Nimet OVAYOLU,; Mehmet KORUK,; Yavuz PEHLİVAN,; Özlem OVAYOLU,; Murat Taner Gülşen, (Turkish Journal of Gastroenterology, 2019)
-